Prospective swallowing outcomes after IMRT for oropharyngeal cancer: Dosimetric correlations in a population-based cohort. (October 2016) - Guo, Gordon Z.; Sutherland, Keith R.; Myers, Candace; Lambert, Pascal; Loewen, Shaun K.; Quon, Harvey C.
Highlights: Four critical swallowing organs at risk are identified during oropharyngeal radiotherapy. Mean doses to the larynx were associated with FT dependence and dietary restrictions. New radiotherapy planning dose constraints are proposed. Abstract: Objectives: To identify dose constraints to preserve swallowing after head and neck (H&N) radiotherapy using prospectively collected functional outcomes. Materials and methods: Stage III–IV oropharyngeal cancer patients were prospectively evaluated using the Royal Brisbane Hospital Outcome Measure for Swallowing and Performance Status Scale for H&N Cancer Patients at pre-treatment and 3, 6, 12, and 24 months after intensity-modulated radiotherapy. Dosimetric parameters were correlated with swallowing function. Results: Ninety-six patients were evaluated with median follow-up of 14.1 months (interquartile range 9.9–26.3). Six patients (8.3%) remained feeding tube (FT) dependent at 12 months. At 2 years, 32.6% tolerated a normal diet without restrictions. Mean doses of 55 Gy to supraglottic larynx, 44 Gy to glottic larynx, 48 Gy to cricopharyngeus, and 44 Gy to esophageal inlet were associated with >25% risk of FT dependence at 6 months. Conclusion: Higher mean doses to the larynx and pharyngo-esophageal junction were associated with longer duration of FT dependence and dietary restrictions.